Evaluasi Radiografi terhadap Kepadatan Tulang Hasil Implan Scaffold 3D Bifasik Kalsium Fosfat Alginat pada Domba Lokal (Ovis aries) - Rahmiati, Dwi Utari; Gunanti, Gunanti; Harlina, Eva (Jurnal Veteriner, 2021)
0 based on chages in size of defect and relative bone density, 2) implant response tissue based on relative muscle density peri implant. The BCP used in this study made from hydroxyapatite (HA) 70, tricalcium phosphate (TCP) 30 and alginate as porogen.  The implant material made in 3D form and have diameter porous 200-400 ìm which similar size with the bone trabecula. This study used three local sheep (Ovis aries) male 1.5 years old, weight average 20 kg. The implant material is grown on the right sheep tibia. As a control, the left tibia is made defective with no implantable material. Evaluate osteogenesis and implant tissue responses using radiography and assess the grey values   of a particular area. Osteogenesis is also assessed based on the size of the defect.  Based on the size of the defect, the right defect shows no significant value. The size of the left defect shows a significant value between day 0 and day 30, and 90. The relative bone density of the right defect shows a significant value between day 7 and 30. In the left defect, the relative bone density shows the significant between 0 and 90. The relative density of the muscle does not show significant values either on the right or left defects.